(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the pledge in civil law and its features using the example of a mortgage agreement. The opinions of domestic legal scholars regarding the legal nature of the mortgage, as well as the features and advantages of the mortgage as a type of pledge are considered.